Contribution of Riparian Vegetation to Water Quality in Spring Water Oras - Yulita Iryani Mamulak; Chatarina Gradict Semiun (Universitas Djuanda, 2021)
Soba Village, West Amarasi Subdistrict, Kupang Regency is located in East Nusa Tenggara Province with abundant natural resources. One of the natural resources is a natural spring with abundant diversity of riparian vegetation. The diversity of riparian vegetation around water sources plays an important role in water quality. This study aimed to identify the diversity of riparian vegetation around springs and to determine water quality. The method used was plot installation, identification of riparian vegetation types, measurement of environmental factors and water quality testing. The results showed that there were 12 species of tree vegetation with a total of 74 individuals, the most common tree species found was Canangan odorata with a relative abundance of 24.32%, followed by Cocos nucifera 18.92%, and Areca sp. 16.22%. Meanwhile, the least species found were Tectona grandis, Mangifera indica, Artocarpus altilis, and Syzygium aqueum with relative species abundance of 1.35%. The results of quantitative analysis of the relative frequency found tree species Areca sp. and Cocos nucifera had the highest value, namely 19.05%. Meanwhile, the highest relative dominance value was found in thespecies Artocarpus altilis. The results of water quality testing with 3 parameters namely physical, chemical and bacteriological showed a COD value of 85.03 mg / L, a total colifrorm of 45 and a total fecal colliform of 230